2017
DOI: 10.7554/elife.23437
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase-dependent phosphorylation of the synaptonemal complex protein SYP-4 regulates double-strand break formation through a negative feedback loop.

Abstract: The synaptonemal complex (SC) is an ultrastructurally conserved proteinaceous structure that holds homologous chromosomes together and is required for the stabilization of pairing interactions and the completion of crossover (CO) formation between homologs during meiosis I. Here, we identify a novel role for a central region component of the SC, SYP-4, in negatively regulating formation of recombination-initiating double-strand breaks (DSBs) via a feedback loop triggered by crossover designation in C. elegans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
116
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(130 citation statements)
references
References 80 publications
11
116
0
Order By: Relevance
“…We hypothesize that PLK-2 localization and activity then spread along the lengths of these SCs via a self-reinforcing feedback loop that in turn results in stabilization of the SC central region along the full length of the SC. This model is reinforced by the recent finding of S. Nadarajan and M. Colaiacovo [33] that SC central region protein SYP-4 is phosphorylated in a PLK-1/2-dependent manner.…”
Section: Discussionmentioning
confidence: 76%
“…We hypothesize that PLK-2 localization and activity then spread along the lengths of these SCs via a self-reinforcing feedback loop that in turn results in stabilization of the SC central region along the full length of the SC. This model is reinforced by the recent finding of S. Nadarajan and M. Colaiacovo [33] that SC central region protein SYP-4 is phosphorylated in a PLK-1/2-dependent manner.…”
Section: Discussionmentioning
confidence: 76%
“…Such an act would further facilitate the transition into metaphase I. Negative regulation of DSB formation by a Polo kinase has recently been reported in the worm (Nadarajan et al , ). We do not currently know whether other members of the Ndt80 regulon facilitate this role of Cdc5, although given the nature of the findings presented here, we speculate that Cdc5 does not act alone.…”
Section: Discussionmentioning
confidence: 95%
“…1 B and C). Two recent studies have shown that the SC progressively becomes more stable throughout the pachytene stage of prophase I, likely through the posttranslational modification of SC proteins (27,28). This gradual switch to a more stable SC could potentially alter the structure as it progresses through meiosis.…”
Section: Resultsmentioning
confidence: 99%